PERAN ORANG TUA DALAM MEMBINA KECERDASAN SPIRITUAL ANAK PADA GENERASI MILLENIAL (STUDI KASUS DI RT 03 RW 16 DESA TEMBOKREJO MUNCAR BANYUWANGI) - Mohammad Afifulloh; Fella Zulfa Zaein; Devi Wahyu Ertanti (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
This study has several objectives, namely, to describe the position of parents in fostering children's spiritual quontients in the millennial generation in Rt 03 Rw 16 Tembokrejo Muncar Banyuwangi, to describe the strategies of parents in fostering spiritual quontients of children in millennial generation on Rt. 03 Rw. 16 Tembokrejo Muncar Banyuwangi, To describe the inhibiting factors of parents in fostering children's spiritual intelligence in the millennial generation on Rt 03 Rw 16 Tembokrejo Muncar Banyuwangi. In conducting this research the approach used by researchers in this study is a qualitative approach. In collecting data, the techniques used by researchers are observation, interview and documentation. Meanwhile, the analysis used is qualitative descriptive analysis. The results showed that there are several roles of parents in fostering spiritual intelligence of children in the millennial generation, namely, the role of role models, educators, motivators, and caregivers. The strategy of parents to increase children's spiritual intelligence is to foster a love for God and His apostles, foster prosocial behavior in children, parents become a good role model for children. The inhibiting factor itself is twofold namely, internal and external factors.